Pengaruh Sifat-Sifat Fisik dan Kimia Bahan Pozolan pada Beton Kinerja Tinggi - Ilham, Ade (Department of Civil Engineering, Diponegoro University, 2005)
High-performance concrete is concrete type resulted from mixing pozzolanic materials into concrete mixture. Materials properties of pozzolan in the form of fine powder, contains high silica and reactivity in a condition. This study uses three type of pozzolan covering fume silica, rice husk ash, and fly ash. Naming of concrete adapted for mixed pozzolan, that is silica fume concrete (SFC), rice husk ash concrete (RHAC), and fly ash concrete (FAC). Materials of concrete mixture use elementary materials (cement, water, coarse aggregate, and fine aggregate) which is equal to air-binder factor between 0.25 - 0.39. The results of indicating that different chemical composition and physical properties of each materials of pozzolan can cause different of fresh concrete, demand of water achieved and also compressive strength reached by SFC, RAHC and FAC. Keywords: silica fume, rice husk ash, fly ash, high-performance concrete, high workability, high-strength concretePermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3923[How to cite: Ilham, A., 2005, Pengaruh Sifat-Sifat Fisik dan Kimia Bahan Pozolan pada Beton Kinerja Tinggi, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 2, pp. 75-85]